Analisis Perawatan Komponen Chamber Box Pada Mesin Laminating Departemen Printing Produksi Kemasan Plastik (Studi Kasus:Pt.Daesang Ingredients Indonesia) - Ridhwan Dwi W; I Nyoman Lokajaya (Jurnal Kendali Teknik dan Sains, 2023)
Miwon Indonesia is one of the companies that started as a company in 1973, the company finally changed the company's name with PT. Daesang Ingredients Indonesia The research method used is Preventive Maintenance, in this study researchers analyzed the time between laminating machine damage to the Chamber Box Heater component, the data taken was the Laminating machine down time data in July – December 2022 The results of analysis and data processing showed that the level of component reliability, namely for the chamber box heater component of 0.5892 occurred on day 5. And while the press roll rewinder component obtained a reliability level of 0.5925 on day 7. And the results of the calculation of costs before preventive maintenance are obtained at a cost of Rp. 47,953,572 per 6 months and costs after preventive maintenance are obtained at Rp. 29,677,876 per 6 months. With a difference of Rp.18,285,696. From the results of preventive maintenance costs, it can reduce maintenance costs at PT. Daesang Ingredients Indonesia than before preventive maintenance calculations are carried out.